PENGARUH AGRESIVITAS PAJAK DAN PROFITABILITAS PERUSAHAAN TEHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Agung Putri Rahmawati; Abdul Rohman (Diponegoro Journal of Accounting, 2019)
This study aims to examines the influence of corporate tax aggressiveness and profitability on corporate social resposibity disclosure (CSRD). Independent variabel used in this study are tax aggressiveness that measured using proxy of effective tax rates (ETR) and profitability that measured using proxy of return on asset (ROA). Dependent variable in this study is the corporate social responsibility disclosure (CSRD).This study used three control variables, include size, capital intensity and leverage.  This study replicated from Lanis and Richardson’s research on (2013). This study used secondary data. The population consists of manufacture companies listed on Indonesia Stock Exchange during 2016. Sampling method used is purposive sampling. The samples were 79 companies. Analysis test using a model of ordinary least square regression analysis.The results of this study show that corporate tax aggressiveness and profitability significantly and positively related to CSRD. This study showed that companies that have a high level of aggressiveness resulting company would disclose CSR greater than the firm that does not tax aggressiveness. This study also showed that companies that have a high level of profitability resulting company would disclose CSR greater than the firm that have a low level of profitability.